Identification of an Inflammatory Biomarker Signature in Plasma-Derived Extracellular Vesicles of Glioblastoma Patients. (1st October 2022) - Cilibrasi, Chiara; Simon, Thomas; Vintu, Marian; Tolias, Christos; Samuels, Mark; Mazarakis, Nektarios; Eravci, Murat; Stewart, Nicholas; Critchley, Giles; Giamas, Giorgios
Abstract: AIMS: Description of effective biomarkers present in biofluids could prove invaluable in GBM diagnosis. Extracellular vesicles (EVs) are essential to intercellular crosstalk in the tumour bulk and circulating EVs have been described as a potential reservoir of GBM biomarkers. Therefore, EV-based liquid biopsies have been suggested as a promising tool for GBM METHOD: Ethical approval was obtained for a prospective study of healthy donors and consenting GBM patients at the University Hospitals Sussex (Brighton). To identify GBM specific proteins, small EVs (sEVs) were isolated from plasma samples using differential ultracentrifugation and validated through Nanoparticles tracking analysis, transmission electron microscopy and detection of known sEVs markers such as CD9, CD63, CD81 and HSP70. sEVs content was characterised through mass spectrometry and bioinformatic tools. RESULTS: Our data indicate the presence of a GBM inflammatory biomarker signature comprising members of the complement and regulators of inflammation and coagulation including VWF, FCGBP, C3, PROS1, and SERPINA1. Bioinformatic analysis highlighted that all potential markers exclusively identified in patient samples had already been linked with either GBM diagnosis, prognosis or associated signalling, suggesting that sEVs protein cargo could mirror the landscape of the original tumour and that selective circulating sEV-derived proteins might be used as hallmarks for GBM patients. CONCLUSION: this study is a step forward in the development of a non-invasive liquid biopsy approach for the identification of valuable biomarkers that could significantly improve GBM diagnosis and, consequently, patients' prognosis and quality of life.